2003
DOI: 10.1067/mod.2003.s0889540602569110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various surface-conditioning methods on the bond strength of metal brackets to ceramic surfaces

Abstract: With the increase in adult orthodontic treatment comes the need to find a reliable method for bonding orthodontic brackets onto metal or ceramic crowns and fixed partial dentures. In this study, shear bond strength and surface roughness tests were used to examine the effect of 4 different surface conditioning methods: fine diamond bur, sandblasting, 5% hydrofluoric acid, and silica coating for bonding metal brackets to ceramic surfaces of feldspathic porcelain. Sandblasting and hydrofluoric acid were further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 0 publications
9
73
2
9
Order By: Relevance
“…7 The second highest shear bond strength was seen in the group conditioned with hydrofluoric acid and silane combination. This result is concurrent with the results of a study conducted by Schmage P et al 5 Zachrisson Y, Zachrisson B and Buyukyilmaz T 2 had conducted a study, in which he concluded that silane application after sandblasting the ceramic surface significantly increases the bond strength of metal brackets bonded to ceramic surface, which is concurrent to the results obtained in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7 The second highest shear bond strength was seen in the group conditioned with hydrofluoric acid and silane combination. This result is concurrent with the results of a study conducted by Schmage P et al 5 Zachrisson Y, Zachrisson B and Buyukyilmaz T 2 had conducted a study, in which he concluded that silane application after sandblasting the ceramic surface significantly increases the bond strength of metal brackets bonded to ceramic surface, which is concurrent to the results obtained in our study.…”
Section: Discussionsupporting
confidence: 82%
“…However, the results obtained in the past studies are contradictory, showing that using silane with hydrofluoric acid does not increase the bond strength. 5 Few of the drawbacks of the previous studies are that some of them have used denture teeth, which are burned at considerably higher temperatures and have properties that differ significantly from the feldspathic porcelains commonly used for porcelain crowns. Furthermore, most of the earlier studies have not included storage in artificial saliva before the testing.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the polished surfaces of VE and LU, and the glazed surfaces of VM and IP, representing the control group, were removed by a fine diamond bur (63 µm). Roughening with diamond burs without silane application was shown to decrease the bond strength compared to roughening with HF acid etching and silane application or Al 2 O 3 air-abrasion and silane application alone [27]. Thus, considering also the low control group results, initial mechanical roughening is crucial prior to bracket bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The shear bond strength of orthodontic brackets bonded with modern bonding materials exceeded 6-8 MPa, thereby rendering sufficient strength for orthodontic treatment [27][28][29][30] . This guideline was based on a report that a minimum bond strength of 5.9-7.9 MPa allowed satisfactory clinical performance and successful clinical bonding in orthodontic treatment 31) .…”
Section: Discussionmentioning
confidence: 99%